(untitled) (Conference Zone, 2022)
This article focuses on the communicative-methodological competence of future foreign language teachers to teach a particular foreign language and implement it as a teacher’s competence. In this context, methodological competence serves as the most important component of a communicative competence of a foreign language teacher.